1988
DOI: 10.1073/pnas.85.7.2260
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a systemic lupus erythematosus-like disease in mice by a common human anti-DNA idiotype.

Abstract: Systemic lupus erythematosus (SLE) is considered to be the quintessential autoimmune disease. It has not been possible to induce SLE in animal models by DNA immunization or by challenge with anti-DNA antibodies. We herewith report a murine model of SLE-like disease induced by immunization of C3H.SW female mice with a common human monoclonal anti-DNA idiotype (16/6 idiotype). Following a booster injection with the 16/6 idiotype, high levels of murine anti-16/6 and anti-anti-16/6 antibodies (associated with anti- Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(146 citation statements)
references
References 13 publications
5
141
0
Order By: Relevance
“…We have previously shown (8)(9)(10)(11)(12)(13)(14) that immunization of naive mice (C3H/W, BALB/c) with a pathogenic anti-DNA idiotype (e.g., 16/6 Id) can induce an SLE-like disease. The mice are injected intradermally with the antibody emulsified in FCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown (8)(9)(10)(11)(12)(13)(14) that immunization of naive mice (C3H/W, BALB/c) with a pathogenic anti-DNA idiotype (e.g., 16/6 Id) can induce an SLE-like disease. The mice are injected intradermally with the antibody emulsified in FCA.…”
Section: Discussionmentioning
confidence: 99%
“…Two-month-old mice (10 per group) were immunized intradermally into the hind footpads with I /Lg of MAb SA-I in Freund's complete adjuvant (FCA; Difco, Detroit, MI). Three weeks later, a booster injection of I /Lg of SA-I in phosphate buffered saline (PBS) was administered to the hind footpads (8). The presence of autoantibodies against single-stranded DNA, dsDNA, poly(l), poly(G), histones (subfractions Hl-H5), cardiolipin, Sm, RNP, SS-A/Ro, SS-B/La, and 16/6 Id idiotype in the serum was determined by enzyme-linked immunosorbent assay (ELISA) (5,6,8,20,21).…”
Section: Methodsmentioning
confidence: 99%
“…Studies by other investigators have shown that immunization with 'pathogenic idiotypes', such as the public idiotype 16/6 (found on many mouse and human anti-DNA antibodies), can induce a lupuslike pathology. 13 The consequences of an anti-idiotypic response with regard to ribonucleoprotein antigens (polyreactive recognition of which was demonstrated by the apoptotic cell specific antibody, as described below) has not been widely explored but is clearly relevant, given the macromolecular nature of the complexes in which these proteins exist. Anti-idiotypic antibodies, generated by immunization of rats with the apoptotic cell specific antibody, were characterized for cellular and antigenic reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Mouse anti-PF4/heparin antibodies were induced using protocols previously described by us to induce other autoantibodies and autoimmune disorders in naive mice [22][23][24][25][26][27][28]31,32]. Briefly, 14-week-old BALB/c mice were immunized intradermally in the hind footpads with each IgG preparation (20 mg emulsified in Freund's complete adjuvant); 15 mice per group were immunized with IgG from either patient (HIT-1 or HIT-2) or with control IgG.…”
Section: Induction Of Mouse Anti-pf4/heparin and Thrombocytopeniamentioning
confidence: 99%